2011
DOI: 10.1159/000327359
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Upregulation of Cyclin D1 and p16INK4a Expression with Low Ki-67 Scores in Multinucleated Giant Cells

Abstract: Background/Aims: Multinucleated giant cells are formed from the fusion of macrophages and are classified into foreign body-type giant cells (FBGCs), osteoclast-type giant cells (OCGCs) and Langhans-type giant cells (LHGCs). OCGCs display upregulated cyclin D1 expression with low Ki-67 activity. However, little is known about the expression of cell cycle regulators in the other types of multinucleated giant cells. We aimed to investigate the cell cycle status of multinucleated giant cells. Methods: The immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…However, as observed in the present case, it is not present in osteoclasts or OGCs [13,14]. As previously reported OGCs showed expression of protein p16 [15], which was absent in melanoma cells. Ki67 expression was limited to melanoma cells with no positivity in OGCs.…”
Section: Discussionsupporting
confidence: 77%
“…However, as observed in the present case, it is not present in osteoclasts or OGCs [13,14]. As previously reported OGCs showed expression of protein p16 [15], which was absent in melanoma cells. Ki67 expression was limited to melanoma cells with no positivity in OGCs.…”
Section: Discussionsupporting
confidence: 77%
“…interleukins 6, 11 and 8, and TNFα; as well as VEGF, placental growth factor (PlGF), hepatocyte growth factor (HGF) and FLt-3 ligand, respectively, some of which can induce proliferation [ 11 , 20 , 21 ]. Earlier studies by others showed the widespread expression of cyclin D1 [ 5 , 6 , 22 24 ] cyclin D3 [ 5 ] and p21 WAF1 [ 6 ], less p16 and scarce Ki67 [ 22 ] in GCs. Still, these data were insufficient to declare replication activity in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…One such factor, receptor activator of nuclear factor kappa-β ligand (RANKL), has been shown to be highly expressed in another case of uterine sarcoma with osteoclast-like giant cells [6]. Additionally, the expression of cyclin D1 has been shown to be upregulated in osteoclast-like giant cells [14,15]. Cyclin D1 expression has also been shown to be associated the formation of giant cells in some studies, including multinucleation and increased chromosome content [15].…”
Section: Discussionmentioning
confidence: 99%